Retroperitoneal Fibrosis and Aortitis as the Initial Findings of Systemic Lupus Erythematosus - Aynur SOYUÖZ; Metin IŞIK; İsmail DOĞAN and Levent KILIÇ and Sedat KİRAZ (Archives of Rheumatology, 2011)
Retroperitoneal fibrosis (RPF) is characterized by progressive connective tissue proliferation which in rare cases forms a periaortic mass. Aortitis is clinically uncommon in systemic lupus erythematosus (SLE), and only one previous case with aortitis has been reported in the literature in living adult patients with lupus. Herein, we report a case with RPF and aortitis as the initial findings of SLE. The patient was admitted to our clinic with severe abdominal pain, nausea, and photosensitivity along with painful, maculopapular lesions on both palms.